2021
DOI: 10.20473/mgk.v10i1.2021.72-79
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Vitamin a Supplementation, Giving Immunization, and History of Infection Disease With the Stunting of Children Aged 24-59 Months in Puskesmas Mulyorejo, Surabaya

Abstract: ABSTRAKLatar Belakang: Stunting merupakan suatu istilah yang menggambarkan kondisi pertumbuhan tinggi badan kurang berdasarkan umur disesuaikan dengan Z-Score (<-2SD). Stunting pada balita dapat diakibatkan oleh kurangnya asupan zat gizi yang diperlukan bagi pertumbuhan anak. Penelitian dilakukan untuk mengetahui hubungan suplementasi vitamin A, pemberian imunisasi dan riwayat penyakit infeksi yakni diare dan ISPA terhadap kejadian stunting.Tujuan: Mengetahui hubungan suplementasi vitamin A, pemberian imuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
1
2
0
3
Order By: Relevance
“…The analysis using the chi square test showed p = 0.906, which means there is no significant relationship between basic immunization and a decrease in the incidence of stunting. The results of this study are directly proportional to the results of the study (9), which shows no significant relationship between basic immunization and the incidence of stunting (9). Study Azriful (2018) also showed the same result; there was no significant relationship between basic immunization and stunting (10).…”
Section: Basic Immunization and Decreasing Incidence Of Stuntingsupporting
confidence: 61%
See 2 more Smart Citations
“…The analysis using the chi square test showed p = 0.906, which means there is no significant relationship between basic immunization and a decrease in the incidence of stunting. The results of this study are directly proportional to the results of the study (9), which shows no significant relationship between basic immunization and the incidence of stunting (9). Study Azriful (2018) also showed the same result; there was no significant relationship between basic immunization and stunting (10).…”
Section: Basic Immunization and Decreasing Incidence Of Stuntingsupporting
confidence: 61%
“…Basic immunization is a way to create active immunity in an individual's body against infectious diseases. Immunization aims to reduce morbidity, disability, and death in diseases that immunization can prevent (9). The analysis using the chi square test showed p = 0.906, which means there is no significant relationship between basic immunization and a decrease in the incidence of stunting.…”
Section: Basic Immunization and Decreasing Incidence Of Stuntingmentioning
confidence: 99%
See 1 more Smart Citation
“…Stunting masalah kurang gizi kronis yang disebabkan oleh asupan gizi yang kurang dalam waktu cukup lama akibat pemberian makanan yang tidak sesuai dengan kebutuhan gizi. Stunting terjadi mulai janin masih dalam kandungan dan baru nampak saat balita berusia dua tahun (2). Faktor kesehatan ibu selama masa kenifasan, Berat Badan Lahir Rendah (BBLR), penyakit infeksi, usia nifas, jumlah balita, jarak kelahiran, merupakan faktorfaktor yang berhubungan terhadap resiko balita balita mengalami stunting (3).…”
Section: Abstract Abstrakunclassified
“…Namun jika terjadi defisiensi vitamin A merupakan salah satu masalah kesehatan serius, khususnya di negara berkembang. Kondisi ini menyebabkan tingginya risiko infeksi gastrointerstinal, yang akan mengganggu penyerapan zat nutrisi pada saluran cerna, terjadi infeksi paru, dan rendahnya respon terhadap vaksinasi, sehingga meningkatkan angka mortalitas pada balitabalita (2). Pemberian mikronutrien untuk balita-balita berupa vitamin A, zat besi dan zic pada masa neonatal sampai akhir masa balita sebagai upaya mencegah stunting (18).…”
Section: Tabel 1 Hasil Analisa Univariat Variabel Penelitianunclassified